Preference of Goat Farmers to Agricultural Extension as a Source of Information and Knowledge in Banjarnegara Regency - Mochamad Sugiarto; Yusmi Nur Wakhidati; Dyah Gandasari (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
Increasing knowledge of farming is essential in increasing goat production in the rural areas of Banjarnegara Regency. Increased knowledge come from many sources, such as extension and non-extension services (other farmers, books, and other government officials). Systematic efforts continue to increase agricultural extension workers' role in providing information and knowledge to goat farmers. This study aims to identify farmers' preference for the agricultural extension as a source of knowledge and analyze the factors that influence the selection of sources of information and knowledge. One hundred sixty goat farmers in Banjarnegara Regency were selected as respondents using a multistage sampling method. The data collected were analyzed using descriptive statistics and logistic regression. The analysis results showed that most of the goat farmers in Banjarnegara Regency (74.37 percent) preferred obtaining knowledge from non-extension sources. In other words, only a small proportion of goat farmers (25.63 percent) prefer to get information and knowledge from agricultural extension workers. Based on the logistic regression analysis, it was found that goat farmers' education and age of farmers were essential factors (P<0.05) in making decisions related to source in obtaining knowledge on raising goats from the agricultural extension or non-agricultural extension workers. Goat farmers in Banjarnegara Regency who have lower education prefer to get information related to goat farming from non-agricultural extension workers. Meanwhile, younger goat farmers tend to get information from non-agricultural extension workers. Therefore, agricultural extension workers have a more strategic role for goat farmers who have higher education and are more mature with adequate goat farming knowledge.